Kimura disease: a rare cause of a recurrent cheek mass in a Jamaican man. Issue 4 (20th April 2021) - Williams, Geoffrey; Neblett, Carlos; Arscott, Jade; McLean, Sheena; Warren, Shereika; Blake, Garfield
Abstract: Kimura disease (KD) is a chronic, inflammatory, benign disorder endemic to Asia that typically manifests as a triad of painless masses in the head and neck region, elevated eosinophils and serum immunoglobulin. It usually affects young men in their second and third decades of life and is rarely seen outside of the orient. This is a report of a case of KD in a young man of African descent who presented with a cheek mass. KD was not included in our differential diagnosis, and this report highlights the need to consider this entity, which can be easily missed due to its rarity in the Western world. There is no cure for the disease, and management includes medical and surgical modalities, but local recurrence or relapse is not uncommon.